2003
DOI: 10.1017/s0022112002003075
|View full text |Cite
|
Sign up to set email alerts
|

The 1[ratio]2 mode interaction in exactly counter-rotating von Kármán swirling flow

Abstract: The flow produced in an enclosed cylinder of height-to-radius ratio of two by the counter-rotation of the top and bottom disks is numerically investigated. When the Reynolds number based on cylinder radius and disk rotation is increased, the axisymmetric basic state loses stability and different complex flows appear successively: steady states with an azimuthal wavenumber of 1; travelling waves; near-heteroclinic cycles; and steady states with an azimuthal wavenumber of 2. This scenario is understood in a dyna… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

18
119
4

Year Published

2006
2006
2020
2020

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 87 publications
(141 citation statements)
references
References 57 publications
(95 reference statements)
18
119
4
Order By: Relevance
“…These vortices have a characteristic size D vortex = 5 cm and they appear simultaneously to the disymmetry of the mean flow. Previous works in similar configurations [7] showed the formation of a static vortex in the equatorial plane (z = 0) for much lower Re, inaccessible with the present configuration.…”
contrasting
confidence: 89%
See 1 more Smart Citation
“…These vortices have a characteristic size D vortex = 5 cm and they appear simultaneously to the disymmetry of the mean flow. Previous works in similar configurations [7] showed the formation of a static vortex in the equatorial plane (z = 0) for much lower Re, inaccessible with the present configuration.…”
contrasting
confidence: 89%
“…These flows have been studied analytically [3,4], numerically [5,6,7] and experimentally [8,9,10]. Recently it has been shown that they can present multistability and memory effects [11].…”
mentioning
confidence: 99%
“…In the range 412 Re 452 unsteady states are predicted theoretically and observed experimentally, consisting in a travelling wave and a modulated wave of the previous one. Increasing again the rotation rate the stable solution is found to be the steady ''Pure mode'', for Re up to 500 by Nore et al (2003Nore et al ( , 2004.…”
Section: Introductionmentioning
confidence: 93%
“…At higher Reynolds number and s ¼ 0 the flow is unstable to azimuthal travelling waves (Gelfgat et al 1996(Gelfgat et al , 2001). The case of cavities with À $ O(1), with the end walls in exact counter rotation, s ¼ À1, has been studied both experimentally and theoretically by Gelfgat et al (1996), Nore et al (2003Nore et al ( , 2004Nore et al ( , 2005. The base flow is axisymmetric and the instability of the steady flow sets up due to free shear layer instabilities through a Kelvin Helmholtz instability.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation